Isolation And Characterization Of Cadmium Resistant Bacteria From Industrial Wastewater - Abbas, Syed Zaghum (2014)
In the last few decades, cadmium removal by biological ways has received great attention. Nevertheless, for the growing of microorganisms that harbor many mechanisms for cadmium sequestration and may have great cadmium removal capacities, only small number of these studies employed in Malaysia. Six bacterial strains were isolated from industrial wastewater of Penang, Malaysia. The strains RZ 1, RZ2, RZ3, RZ4, RZ5 and RZ6 were identified as Pantoea sp. RL32.2, Salmonella enterica, Enterobacter sp. OCPSB 1, Enterobacter mori, Enterobacter sp. WS 12 and Pseudomonas sp. M3 respectively, based on morphological, biochemical, physiological observation and 16S rDNA sequence analysis. All the six strains showed optimum growth and cadmium removal at 7.0 pH and 35°C temperature. The strains RZl, RZ2, RZ3, RZ4, RZ5 and RZ6 removed 89.89%, 82.10%, 89.14%, 87.75%, 85.11% and 81.89% of cadmium, respectively. The cadmium removal capacities by all the strains were affected by temperature and pH. The minimum inhibitory concentrations of the strains RZl, RZ2, RZ3, RZ4, RZ5 and RZ6 were 750 ug/ml., 410 ug/ml., 550 ug/ml.; 450 ug/ml., 500 ug/rnl. and 550 ug/ml, respectively.